Comparative metagenomics and characterization of antimicrobial resistance genes in pasteurized and homemade fermented Arabian laban. (November 2020) - Yasir, Muhammad; Bibi, Fehmida; Hashem, Anwar M.; Azhar, Esam I.
Graphical abstract: Highlights: Homemade laban has higher bacterial diversity, probiotics, and pathogens. Antimicrobial resistance genes and transposases were found in homemade laban. Carbohydrate metabolism and vitamin biosynthesis pathways were detected in the laban metagenomes. Strains closely related to S. thermophilus were identified as a starter culture. Abstract: The aim of this study was to investigate bacterial diversity and function in a fermented milk drink called laban, which is traditionally served in the Middle East, Africa, and Indian subcontinent. Pasteurized laban (LBP) and unpasteurized, homemade, raw laban (LBR) underwent 16S rRNA gene amplicon and shotgun sequencing to analyze their bacterial community, presence of antimicrobial resistance genes (ARGs), and metabolic pathways. This study highlighted relatively greater diversity in LBR bacterial populations compared to LBP, despite containing similar major taxa that consisted primarily of Firmicutes followed by Proteobacteria, Bacteroidetes, and Actinobacteria. The dominant species, Streptococcus thermophilus, was relatively more abundant in LBP (80.7%) compared to LBR (47.9%). LBR had increased diversity and higher relative abundance of several known probiotic bacteria, such as Streptococcus salivarius and Lactococcus lactis, whereas Lactobacillus acidophilus was detected at a higher abundance in LBP. Pathogens like Acinetobacter baumannii, Streptococcus pneumoniae, Streptococcus pyogenes, and Escherichia coli had lower abundance in LBP compared to LBR. Thirty-three ARGs were detected in LBR compared to nine in LBP and are responsible for resistance to 11 classes of antibiotics. A significant proportion of the metagenomes from both types of laban were assigned to housekeeping functions, such as amino acid metabolism, translation, membrane transport, and carbohydrate metabolism. LBR demonstrated increased diversity in probiotics and metabolic functions compared to LBP. However, the relatively high diversity of pathogenic and opportunistic bacteria and ARGs in LBR raises safety concerns and highlights the need for a more hygienic environment for the processing of homemade fermented dairy foods.